2003
DOI: 10.1079/bjn20031006
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high-carbohydrate meals with different glycaemic indices on substrate utilisation during subsequent exercise

Abstract: The present study was designed to examine the effects of mixed high-carbohydrate meals with different glycaemic indices (GI) on substrate utilization during subsequent exercise. Nine healthy male recreational runners (age 26·8 (SEM 1·1) years, body mass 74·7 (SEM 2·4) kg, V O 2 max 58·1 (SEM 1·7) ml/kg per min) completed three trials: high-glycaemic-index meal (HGI), low-glycaemic-index meal (LGI) and fasting (FAST), separated by 7 d. The test meals contained 2 g carbohydrate/kg body mass, they were isoenerget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
108
7
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(141 citation statements)
references
References 36 publications
21
108
7
5
Order By: Relevance
“…This is in agreement with previous studies that have investigated the effect of a single pre-exercise meal or food with differing GI values on substrate metabolism during exercise (Wee et al, 1999;Wu et al, 2003;. It has been suggested that the chronic intake of a LGI diet results in changes in fuel partitioning and substrate oxidation due to reduced insulinaemia in the postprandial period.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in agreement with previous studies that have investigated the effect of a single pre-exercise meal or food with differing GI values on substrate metabolism during exercise (Wee et al, 1999;Wu et al, 2003;. It has been suggested that the chronic intake of a LGI diet results in changes in fuel partitioning and substrate oxidation due to reduced insulinaemia in the postprandial period.…”
Section: Discussionsupporting
confidence: 91%
“…Reduced hyperinsulinaemia during the postprandial period following the LGI meal reduces the suppression of fat oxidation compared to when a HGI meal is consumed. This allows a shift in substrate utilization toward fat oxidation during the subsequent exercise as well as providing a sustainable source of CHO (Wu et al, 2003). The results of Figure 5 Blood lactate concentrations (mmol l À1 ) during the HGI and LGI trials (mean7s.e.m.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substituting a HGI breakfast for a LGI breakfast may, therefore, be particularly beneficial for OW individuals through increased glycemic control (Willett et al, 2002), fat oxidation (Stevenson et al, 2009) and satiety (Ludwig et al, 1999). However, the majority of studies investigating the impact of GI on fat oxidation have included endurance trained or recreationally active adults as participants (Wu et al, 2003;Stevenson et al, 2006) and we are unaware of similar studies including OW individuals or young people, despite well-recognised differences in metabolism between adolescents and adults (Riddell et al, 2008). Therefore, we examined the effect of mixed breakfast meals providing HGI or LGI carbohydrates on metabolic responses and substrate utilisation during rest and exercise in OW and non-overweight (NO) adolescent girls.…”
Section: Introductionmentioning
confidence: 99%